Climatic indicators regarding the rest period of sour cherry - Ladányi, M.; Persely, Sz.; Nyéki, J.; Szabó, T.; Soltész, M.; Szabó, Z. (International Journal of Horticultural Science, 2010)
Sour cherry production in the world is increasing gradually. Profitable production, i.e. yield, depends largely on weather conditions. If Hungary wishes to keep up with the most successful countries, attention should be paid to the weather during the dormancy period, being definitely decisive from the points of view of quality as well as quantity. In order to predict the expected risk factors, characterisation of the most important weather parameters is necessary. For that purpose, the database of the Institute of Research and Extension Service for Fruit Growing at Újfehértó Ltd. has been utilised. Records of weather conditions were collected throughout the period 1984-2005, i.e. daily minimum, maximum and mean temperatures (°C), and phenological diary of sour cherry varieties ’Újfehértói fürtös’, ’Kántorjánosi’ and ’Debreceni bôtermô’. For the future expectations study we have used the RegCM3.1 regional climate model with 10 km resolution. Data of 4 indicators have been traced: Average temperatures, Number of days without frost, Maximum length of periods without frost, Maximum length of frosty period. On the one hand, we surveyed the changes; on the other hand, estimates have been attempted for the future changes expected during the following decades.